Análise genética de genitores de soja Glycine max (L.) Merril nas gerações de F1 e F2 visando melhoramento para semeadura antecipada - Santos, Rodnei dos (2019)
The soybean crop is of extreme economic importance for the state of Paraná. However, a trend of the state's rural producers is the anticipation of sowing soybeans to the early days of agricultural zoning. This behavioral change raises the alert about the need for intensified research at this point, especially research related to genetic improvement, which aims to obtain cultivars adapted to early sowing. Thus, the objective of this work was to characterize morphologically the genetic dissimilarity of nine cultivars in early sowing, promoting their grouping, besides estimating genetic parameters of genotypes and F1 and F2 generations through partial diallel crosses, indicating the combinations and the most promising cultivars to obtain favorable recombination for early sowing aiming at increasing grain yield. The cultivars presented significant genetic dissimilarity, indicating the existence of variability for the traits evaluated in early sowing, being possible to separate them in two distinct groups. The work allowed the identification of cultivars that can be used in artificial crossings of high heterosis. The traits that most contributed to genetic dissimilarity were days from emergence to flowering and final plant height. The cultivars 53I54RSF IPRO, 5958RSF IPRO and 50I52RSF IPRO stood out from the others, combining high yield average, specific combining ability (CEC) and high overall combining capacity (CGC) for grain yield (RG) in early sowing. The combination of these cultivars indicates to be promising to compose blocks of intersections for presenting high productive potential in early sowing through allelic complementarity.